Peran Guru dalam Internalisasi Literasi Digital Keagamaan bagi Siswa - Munawir, Munawir; Aliyah, Himmatul; Bidari, Ratna Ayyu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Religious literacy is a crucial competency for individuals in the twenty-first century, particularly in responding to the rapid development of digital technology that significantly influences religious understanding, attitudes, and practices. Nevertheless, Indonesia continues to face challenges related to low levels of literacy, including religious literacy and digital literacy among students. This study aims to examine and analyze the role of teachers in cultivating digital religious literacy among students in the twenty-first century so that they are able to engage with digital religious information in a critical, ethical, and responsible manner. The research employs a Systematic Literature Review (SLR) method by analyzing various academic sources, including reputable journal articles, scholarly books, official regulations, trusted websites, and other relevant literature related to religious literacy, digital literacy, and the role of teachers in education. The findings indicate that teachers play a strategic role in developing digital religious literacy through curriculum integration, the application of critical digital pedagogy, modeling ethical behavior in digital media use, and guiding students in evaluating the credibility of religious information in digital spaces. Furthermore, teachers contribute to fostering students’ reflective abilities, religious moderation, and tolerance within digital religious discourse. The implications of this study highlight the importance of strengthening teachers’ digital and religious competencies through continuous professional development to address the challenges of digital religious literacy in the digital era.